Precision in Liver Surgery - Dong, Jiahong; Yang, ShiZhong; Zeng, Jianping; Cai, Shouwang; Ji, Wenbin; Duan, Weidong; Zhang, Aiqun; Ren, Weizheng; Xu, Yinzhe; Tan, Jingwang; Bu, Xiangyang; Zhang, Ning; Wang, Xuedong; Wang, Xianqiang; Meng, Xiangfei; Jiang, Kai; Gu, Wanqing; Huang, Zhiqiang (Seminars in Liver Disease, 2013)
Continuous theoretical and technological progress in the face of increasing expectations for quality health care has transformed the surgical paradigm. The authors systematically review these historical trends and propose the novel paradigm of “precision surgery,” featuring certainty-based practice to ensure the best result for each patient with multiobjective optimization of therapeutic effectiveness, surgical safety, and minimal invasiveness. The main characteristics of precision surgery may be summarized as determinacy, predictability, controllability, integration, standardization, and individualization. The strategy of precision in liver surgery is to seek a balance of maximizing the removal of the target lesion, while maximizing the functional liver remnant and minimizing surgical invasiveness. In this article, the authors demonstrate the application of precision approaches in specific settings in complex liver surgery. They propose that the concept of precision surgery should be considered for wider application in liver surgery and other fields as a step toward the ultimate goal of perfect surgery.
Keywords: precision surgery; liver surgery; certainty; multiobjective optimization